In vitro rooting of shoots and acclimatization of Agave potatorum Zucc. plants - Bautista-Castellanos, Ariadna Ivón; Enríquez-del Valle, José Raymundo; Velasco-Velasco, Vicente Arturo; Rodríguez-Ortiz, Gerardo (Ecosistemas y Recursos Agropecuarios, 2021)
Agave potatorum Zucc., is a wild or cultivated monocotyledonous species, used to make mescal, and due to its growing demand it is collected exces- sively. The objective was to know the effect of the concentration of mineral salts, indole-acetic acid (IAA) and indole-3-butyric acid (IBA) in the culture medium, Mc, on the in vitro rooting of shoots, the acclimatization and growth of the micropropagated plants that received different doses of fertilization in the nursery. The work consisted of two stages: 1) shoots grown for 66 days in Mc with different concentration of inorganic salts MS (75 or 100%), auxin (IAA or IBA) alone or combined in concentrations of 0, 0.1, or 0.5 mg L−1. In stage 2, groups of plants originating from rooted shoots were transferred to trays with 33% peat-66% perlite substrate, and were fertirrigated for 90 days with different doses of nutrient solution, SN (25, 50, or 100%) of the Steiner formulation. Between 94 and 96% of the shoots formed roots in Mc with 0.1 to 0.5 mg L−1 of IBA, after 13 to 37 days of incubation, the better response than the shoots in Mc without auxins, or with IAA. When the plants were 90 days in the nursery, from 87 to 90% were adapted. The plants fertirrigated with SN-50% developed an average of 8.9 leaves, with a máximum length of 8.4 cm, the stem of 10.27 mm in diameter, fresh weight of 4.15 g and dryweight of the plant of 0.31 g.